Electrical and Thermal Behavior of Copper-Epoxy Nanocomposites Prepared via Aqueous to Organic Phase Transfer Technique - Mohd Hirmizi, N. H.; Abu Bakar, M.; Tan, W. L.; Abu Bakar, N. H. H.; Ismail, J.; See, C. H. (Hindawi Publishing Corporation, 2012)
The preparation, electrical, and thermal behaviors of copper-epoxy nanocomposites are described. Cetyltrimethylammonium bromide- (CTAB-) stabilized copper (Cu) particles were synthesized via phase transfer technique. Isopropanol (IPA), sodium borohydride (NaBH4), and toluene solution of diglycidyl ether of bisphenol A (DGEBA) were used as transferring, reducing agent, and the organic phase, respectively. The UV-Vis absorbance spectra of all the sols prepared indicate that the presence of Cu particles with the particles transfer efficiency is ≥97%. The amount, size, and size distribution of particles in the organosol were dependent on the content of organic solute in the organosol. The composites were obtained upon drying the organosols and these were then subjected to further studies on the curing, thermal, and electrical characteristic. The presence of Cu fillers does not significantly affect the completeness of the composite curing process and only slightly reduce the thermal stability of the composites that is >300◦C. The highest conductivity value of the composites obtained is 3.06 × 10−2 S cm−1.